PROFESSIONAL POSITION OF HER ROLE IN INTERACTION TEACHERS AND STUDENTS IN LESSON - Shcherbyna, S.M. (Pedagogy of Higher and Secondary Education, 2006)
The author of the article highlights the influence of active professional position on the psychological climate of lesson.